Analysis of Sound Devices among Selected Shakespearean, Spenserian, and Petrarchan Sonnets - Mago, Ivy; Ampaso, Nor Ain; Pedores, Remy Jean; Tabon, Xyrish Alexandrea; Nery, Andrea; Tolentino, Jade; Dumlao, Kate Camille; Naol, Crisheille (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explored the use of sound devices in selected Shakespearean, Spenserian, and Petrarchan sonnets. A qualitative comparative analysis was conducted on three selected sonnets about love and death. The analysis revealed that all three sonnets utilize accent, rhythm, meter, and rhyme to create a structured musical quality. Additionally, all three forms employ alliteration, consonance, assonance, and repetition to various degrees, influencing the poem's rhythm, memorability, and emotional impact. All three forms of sonnets employed both euphony and cacophony with some lines overlapping each other to create a contrast that will build tension and anticipation. Finally, none of the sonnets employed onomatopoeia. This research highlights the diverse uses of sound devices within different sonnet forms enriching the understanding of how these poems achieve their artistic effects. The research suggests that investigating the correlation between sound devices with other sonnets under the three forms would be beneficial for future studies as it will provide a general pattern of what sound devices the three forms prefer using